Metal contaminants and chloramphenicol in Litopenaeus vannamei and Penaeus silasi at various supply chain stages in Johor Bahru, Malaysia and their health risk assessment - Nurazira Anuar; Naji Arafat Mahat; Ida Idayu Muhamad; Aemi Syazwani Abdul Keyon; Mohamad Afiq Mohamed Huri; Nor Alafiza Yunus; Dayang Norulfairuz Abang Zaidel; Noor Azira Abdul-Mutalib; Son Radu; Aida Rasyidah Azman (Journal of King Saud University: Science, 2023)
Objectives: This present research evaluated the concentrations of metal contaminants (As, Pb, Cd and total Hg) and chloramphenicol as prescribed by the Malaysian Food Act (1983) and Regulations (2021) in Penaeus silasi and Litopenaeus vannamei shrimps sampled from the different supply chain stages (landing sites, major markets and grocers) in Johor Bahru, Johor, Malaysia at six sampling intervals. Methods: Graphite furnace atomic absorption spectrometer and flow injection mercury/hyride system were used to determine the concentration of As, Pb and Cd as well as total Hg, respectively. Enzyme-linked immunosorbent assay was used to determine the concentration of chloramphenicol. Results: The median As and Cd concentrations during the six sampling intervals ranged between below detection limit-167.5 mg/kg and 0.46 mg/kg, respectively. The total Hg concentrations ranged between 0.02 and 1.13 mg/kg. Although Pb and chloramphenicol were not detected, As and total Hg concentrations varied significantly across sampling intervals (P < 0.05), exceeded the maximum permitted proportions prescribed by the Malaysian law. Identified as P. silasi, shrimps from landing sites Mersing and Pontian had significantly higher As and total Hg concentrations than those of L. vannamei from major markets and their surrounding grocers (P < 0.05). Alarmingly, Hazard Index for P. silasi from landing sites Mersing and Pontian as well as L. vannamei from major markets and grocers exceeded 1.00. Conclusion: Hence, formulating suitable intervention programs and devising efficient removal technologies are paramount for benefiting the public at large.